Analysis of the suspended sediment transport estimation at different time scales in Mediterranean watershed, case of Wadi El Maleh (North - West of Algeria) - Benselama, Oussama; Mazour, Mohamed; Hasbaia, Mahmoud; Djoukbala, Omar; Mokhtari, Sakher (Journal of Mediterranean Earth Sciences, 2019)
The present paper aims to estimate and analysis the variability of the suspended sediment transport in Wadi El Maleh watershed at different time scales. The used sets data consist of the measured instantaneous water discharge and suspended sediment concentration, they are recorded in the gauging station situated at the outlet of the watershed during 17 years. The results show that the sediment rating curve explains more 74% of the variance for the whole data (pairs Q - C). The estimated specific soil erosion is about 294,29 t/km2/year. The analysis of the evolution of concentration and the quantification of sediment yield have shown that the sediment supply occurs mainly during extreme events, one flood in January 1988 generated more than 92% of total sediment yield rate. In wet season, we recorded 78% of the total soil loss rate, the most part of sedimentary dynamics for Wadi El Maleh is observed in winter with 45,41%. The suspended sediment transport in this season remains the highest, significantly exceeding the other seasons. These values are very close to that observed in other regions with similar hydrological regimes.